2019
DOI: 10.31248/jasvm2019.134
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass characteristics of West African dwarf (WAD) goats fed selected forages in Akwa Ibom State

Abstract: The potential of selected forages was evaluated using West African Dwarf (WAD) goats. Six forages namely, Andropogon tectorum, Panicum maximum, Aspilia Africana, Gmelina arborea, Alchornea cordifolia and Bambusa vulgaris designated as T1 to T6, respectively were the only feed source used for the study. Thirty West African Dwarf goats aged 8 to 9 months, with an average bodyweight of 9.17 to 10.10 kg were used for the study. The goats were assigned to six treatment groups based on the forages used in a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…Drinking frequency was substantially (p<0.05) greater in the conventional housing system compared to the loose housing system in the current findings (Table 3), which may be attributed to the strong association between feed intake and water intake. The results are also in line with Mohammad et al, 2014;Abdel-Hamid, 2017 andEyoh et al, 2019, as they reported that the majority of goats seen drinking at intensive management systems was subjected to behavioral redirection. However non-significant effect of different housing system on drinking behavior was reported by Keane et al (2017) in heifers and Norouzian et al (2017) in sheep.…”
Section: Drinkingsupporting
confidence: 88%
See 2 more Smart Citations
“…Drinking frequency was substantially (p<0.05) greater in the conventional housing system compared to the loose housing system in the current findings (Table 3), which may be attributed to the strong association between feed intake and water intake. The results are also in line with Mohammad et al, 2014;Abdel-Hamid, 2017 andEyoh et al, 2019, as they reported that the majority of goats seen drinking at intensive management systems was subjected to behavioral redirection. However non-significant effect of different housing system on drinking behavior was reported by Keane et al (2017) in heifers and Norouzian et al (2017) in sheep.…”
Section: Drinkingsupporting
confidence: 88%
“…Variations in body length, height at wither, and heart circumference between two housing systems viz, conventional and loose housing systems may be caused by variations in body growth in each system, which is a sign of the animals' degree of comfort and production. The same results were reported by Thiruvenkadam et al, 2009;Birteeb et al, 2015;Eyoh et al, 2019 in goats reared under different management systems. Contrary to this, Tiezzi et al (2019) found non-significant effect on morphological traits of goats raised under conventional housing systems.…”
Section: Morphological Traitssupporting
confidence: 87%
See 1 more Smart Citation